Handbook of research on trends and issues in crime prevention, rehabilitation, and victim support - Balloni, Augusto; Sette, Raffaella (Advances in criminology, victimology, serial violence, and the deep web (ACVSVDW) book series., 2020)
"This book explores good practices and innovative experiences on crime prevention, victim support, and rehabilitation"--Provided by publisher.